Vertisols infiltration rate and model performance evaluation of various land-use conditions during Southern Ethiopia's dry season - Edmealem Temesgen; Destaw Akil; Guchie Gulie (Journal of Digital Food, Energy & Water Systems)
The research was conducted on the field and models of vertisol soil types under varied land in southern Ethiopia's semi-arid Arba Minch university research centre site to measure infiltration and determine infiltration rates. The infiltration rate and model performance evaluation of the specific land use conditions affect the design and evaluation of surface and sub-surface irrigation methods. The infiltration rate is investigated on two different types of land (vegetable-covered land and bare land) and two different types of models (Horton and Kostiakov models). The experimental infiltration depth of the above soil conditions is measured using a double-ring infiltrometer. The research aims to figure out the field-measured infiltration rate, model infiltration rates, and basic infiltration rate, identify the impact of infiltration factors on infiltration rate, and find the best-fitted infiltration model. The findings from multiple infiltration models were compared with actual field data. The graphs of infiltration were generated to find the best fitting model for a certain vertisol soil type and two lands. The determination, correlation coefficient, bias, root mean square error (RMSE), model efficiency, determination coefficient (R2), slope, correlation coefficient (r), average percentage error, and the gradient were the performance indicators examined for the optimum fitting of the model. The Kostiakov model's results are the best fit to observe field data for estimating infiltration rates at any given period in the research region by taking into account the infiltration numerical software performance indicators. The vegetable cover land infiltration rate is higher than un-disturbed bare land.